Cytosine deaminase를 포함한 사람의 중간엽 줄기세포를 이용한 유전자 치료 연구 - 김왕준 (The Graduate School, Ajou University, 2009)
ABSTRACT Background and Aim: Stem cell transplantation offers potential gene therapy for brain tumors. However, this approach has received little attention as a treatment for gastrointestinal tumors. In the present study, we explored the possibility of human bone marrow derived mesenchymal stem cells (hMSC) producing cytosine deaminase (CD), followed by systemic 5-fluorocytosine (5-FC) administration, showing an antitumor effect on a mouse gastric cancer xenograft. Methods: We first explored the ability of hMSC, coated with fluorescent dye, to migrate to human gastric cancer MKN45 cells in vitro and in vivo. We then used hMSC in which a gene expressed the prodrug-activating enzyme CD, which can convert the prodrug 5-FC into the cytotoxic agent 5-fluorouracil (5-FU), and further investigated the potential of these cells to deliver the CD gene and to reduce tumor growth in nude mice. The migratory capacity of hMSC was confirmed by an in vitro migration assay, as well as in an in vivo model of nude mice bearing subcutaneous tumors of MKN45 cells when hMSC were injected. Results: The migration ability of hMSC towards MKN45 cells was confirmed by migration assay. Effective conversion of 5-FC to 5-FU by hMSC transfected with the CD gene (CD-hMSC) showed therapeutic anticancer potential in a MKN45 cell co-culture system, as confirmed by thin layer chromatography, MTT assay in vitro. Conclusion: The CD-hMSC system showed anticancer therapeutic potential, and minimized the side-effects of 5-FU.
학위논문(박사)--아주대학교 일반대학원 :분자과학기술학과,2009. 8
Keywords: gene therapy; cytosine; deaminase-producing; 중간엽; 줄기세포; 유전자 치료